2012
DOI: 10.1016/j.molcel.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Translesion Transcription by RNA Polymerase II and Its Role in Cellular Resistance to DNA Damage

Abstract: UV-induced cyclobutane pyrimidine dimers (CPDs) in the template DNA strand stall transcription elongation by RNA polymerase II (Pol II). If the nucleotide excision repair machinery does not promptly remove the CPDs, stalled Pol II creates a roadblock for DNA replication and subsequent rounds of transcription. Here we present evidence that Pol II has an intrinsic capacity for translesion synthesis (TLS) that enables bypass of the CPD with or without repair. Translesion synthesis depends on the trigger loop and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
165
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(181 citation statements)
references
References 38 publications
13
165
2
1
Order By: Relevance
“…Based on experimental observations, several models have been proposed for the way cells respond when the progression of an actively transcribed RNAPII is blocked by DNA lesions and for the fate of the polymerase in cases of faulty repair. These involve stalling of RNAPII and its dislocation from the damaged chromatin, either by reverse translocation (backtracking) leading to RNAPII arrest or by dissociation from the chromatin and subsequent degradation of the polymerase, as well as lesion bypass by RNAPII Marietta and Brooks 2007;Fousteri and Mullenders 2008;Cheung and Cramer 2011;Walmacq et al 2012;Wilson et al 2012). RNAPII has been shown to stall at CPDs for at least 20 h in vitro (Selby et al 1997) and for more than 48 hours in vivo in Csb-deficient mouse cells after UV-C irradiation (Garinis et al 2009).…”
Section: Transcriptional Arrest and Its Coupling To Dna Damage Responmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experimental observations, several models have been proposed for the way cells respond when the progression of an actively transcribed RNAPII is blocked by DNA lesions and for the fate of the polymerase in cases of faulty repair. These involve stalling of RNAPII and its dislocation from the damaged chromatin, either by reverse translocation (backtracking) leading to RNAPII arrest or by dissociation from the chromatin and subsequent degradation of the polymerase, as well as lesion bypass by RNAPII Marietta and Brooks 2007;Fousteri and Mullenders 2008;Cheung and Cramer 2011;Walmacq et al 2012;Wilson et al 2012). RNAPII has been shown to stall at CPDs for at least 20 h in vitro (Selby et al 1997) and for more than 48 hours in vivo in Csb-deficient mouse cells after UV-C irradiation (Garinis et al 2009).…”
Section: Transcriptional Arrest and Its Coupling To Dna Damage Responmentioning
confidence: 99%
“…However, this is probably a rare event as the presence of a CPD in the active site of RNAPII has been shown to strongly disfavor forward translocation of RNAPII ). Under certain conditions and likely with low frequency, bypass of helix distorting lesions such as CPDs and cyclo-dA may occur in yeast (Walmacq et al 2012) and in NER deficient human cells (Marietta and Brooks 2007). Yeast RNAPII was shown to bypass CPDs via an intrinsic ability to perform errorfree translesion synthesis, whereas bypass of bulky lesions in human XP-A cells resulted not only in transcription mutagenesis but also in nonmutant transcripts.…”
Section: Transcriptional Arrest and Its Coupling To Dna Damage Responmentioning
confidence: 99%
“…Two recent pol II elongation complex structures containing either CPD or CydA lesions shed new structural insights into answering this question. 12,17 Strikingly, despite significant structural differences between CPD and CydA DNA lesions, it was found that both DNA lesions are accommodated at a similar location at the pol II active site. Both DNA lesions are stuck above the bridge helix and arrested at essentially a "half-way" position of template translocation from the downstream canonical iC2 position to iC1 position.…”
mentioning
confidence: 95%
“…These DNA modifications and lesions may lead to different outcomes depending on their chemical nature, which may lead to transcriptional mutagenesis, transcriptional arrest, transcription coupled repair pathway, or pol II ubiquitylation. [11][12][13][14] In all of these cases, pol II is proposed to function as a specific sensor to sense DNA modifications and lesions through specific interactions with the pol II active site. 15 Over the last few years, significant new structural insights were obtained in the understanding of how pol II interacts with different types of DNA lesions at the active site.…”
mentioning
confidence: 99%
See 1 more Smart Citation